Confronting ageism: The potential of intergenerational contemporary art events to increase understandings of older adults and ageing. (15th July 2018) - Cook, Peta S; Vreugdenhil, Anthea; Macnish, Brienna
Abstract : Objective: To explore the impact of an innovative intergenerational art event showcasing retirement village life on attendees' understandings of older adults and ageing. Methods: A survey of 93 art event attendees was conducted immediately after 16 sessions of the event (78% response rate). Respondents reported on their event experience and its impact on their understandings of older adults and attitudes towards ageing. Analysis of Variance (ANOVA) used to test for differences between age groups (18–34, 35–64 and 65+ years). Results: Over 90% of attendees reported the art event helped them develop an understanding of the lives of older people, with the greatest impact on young and middle‐aged adults. The majority of young and middle‐aged adults, however, expressed concern about their own ageing. Conclusion: Results suggest that intergenerational art events have the potential to increase understandings of older adults and their lives, but this may not translate into personalised comfort with ageing.